Detailed low frequency noise assessment on GAA NW n-channel FETs. (August 2021) - Cretu, B.; Bordin, A.; Simoen, E.; Hellings, G.; Linten, D.; Claeys, C.
Highlights: The carrier number fluctuations mechanism dominates the 1/f noise (300K-340K). Temperature analysis of the GR noise allowed to prove the existence of traps located in the Si film and to identify them. Correlation between the identified traps and the related technological steps were made. Abstract: Low frequency noise (LFN) studies are carried out on n-channel gate all around nanowire (GAA NW) FETs. Measurements both as a function of applied polarisation at fixed temperature and conserving the same drain current bias points as a function of temperature are performed, to investigate the predominant flicker noise fluctuation mechanism and to execute low frequency noise spectroscopy allowing to identify the active traps in the depletion area of the devices. The good correlation between the normalized drain current noise SId / Id 2 and the transconductance to drain current ratio squared (gm /Id ) 2 enables to establish that the 1/ f noise is related to the carrier number fluctuations mechanisms for all investigated temperatures. The study of the generation recombination (GR) noise as a function of temperature confirms the presence of a GR component for which the characteristic frequency is independent on the applied voltage and present variation with the temperature, suggesting that they are related to active traps located in the Si film. Active traps related to hydrogen and divacancies were identified.